2017
DOI: 10.4103/jnrp.jnrp_474_16
|View full text |Cite
|
Sign up to set email alerts
|

Guillain–Barre Syndrome in Postpartum Period: Rehabilitation Issues and Outcome – Three Case Reports

Abstract: We report three females who developed Guillain–Barre Syndrome in postpartum period (within 6 weeks of delivery) and were admitted in the Neurological Rehabilitation Department for rehabilitation after the initial diagnosis and treatment in the Department of Neurology. The first case, axonal variant (acute motor axonal neuropathy [AMAN]) had worst presentation at the time of admission, recovered well by the time of discharge. The second case, acute motor sensory axonal neuropathy variant and the third case, AMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 10 publications
0
6
0
3
Order By: Relevance
“…Overall incidence of GBS worldwide was reported only to be 1.1-1.8/100,000 in a literature review of the epidemiology of GBS 13 , so in this case also it is very much unlikely that GBS occurred due to pregnancy. However an important aspect according to pathophysiology is to differentiate whether GBS following COVID-19 is a para-infectious response or a true post infectious immune mediated response 14,15 .…”
Section: Discussionmentioning
confidence: 76%
“…Overall incidence of GBS worldwide was reported only to be 1.1-1.8/100,000 in a literature review of the epidemiology of GBS 13 , so in this case also it is very much unlikely that GBS occurred due to pregnancy. However an important aspect according to pathophysiology is to differentiate whether GBS following COVID-19 is a para-infectious response or a true post infectious immune mediated response 14,15 .…”
Section: Discussionmentioning
confidence: 76%
“…GBS worsens in the postpartum period due to restoration of cellular immunity, with an increase in delayed type of hypersensitivity which was adaptively depressed during pregnancy [8]. Gupta et al reported 3 cases of GBS, one appeared immediately after cesarean section and other two occurred between the 5th and 6th week postpartum [9]. In a study which analyzed the records of 47 patients with pregnancy and GBS, one patient presented in first trimester, seven patients (14.89%) were in second trimester, 15 (31.2%) were in third trimester and remaining 24 (51%) were presented in postpartum especially within 2 weeks (sharma).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and management of GBS in pregnancy and postpartum is similar to that in the general population [ 5 ]. In some cases, the management of this rare presentation requires a transfer to intensive care units for artificial ventilation [ 18 ]. To the best of our knowledge, only one case of GBS in a postpartum patient after cesarean section under spinal anesthesia has been described; however, there is no strong evidence supporting the association of neuraxial anesthesia and GBS [ 19 ].…”
Section: Discussionmentioning
confidence: 99%